Thermodynamic Studies of Y(III), La(III), Ce(III) and Sm(III) Complexes of 5-Hydroxy-2-methyl-1,4-naphthalenedione - KUMAR, MUKESH; KAMRA, ANITA; SINGH RATHEE, NIRANJAN (Asian Journal of Chemistry, 2010)
The pH-metric and thermodynamic stability have been carried out for yttrium(III), lanthanum(Ill), cerium(III) and samarium(llI). complexes of 5-hydroxy-2-methyl-1,4-naphthalenedione (plumbagin). Three molecules of plumbagin (5-hydroxy-2-methyI-1,4-naphthalenedione) react with these metal ions in solution phase (50% aqueous EtOH, 0.1 M KNO3 ionic strength) at varied temperatures. The data for yttrium(llI), lanthanum(III), cerium(III) and samariurn(III) with plumbagin systems reveals a decrease in the value of log pkH, log k1, log k2 and log k3 with the increase in temperature; this indicates that the lower temperature is favourable for complexation due to the decrease in the number of collisions and kinetic energy of the molecules and hence their stabilities are lowered.